1999
DOI: 10.1080/135467999387289
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Automaticity in the Basic Addition Facts as a Characteristic of Arithmetic Learning Problems and Instructional Needs

Abstract: Computational facility and the relationship between automaticity or efficient processing of addition facts and success in more complex tasks were examined in a cross-sectional study of 109 children from Grades 3 through 6. Latency data and interview protocols enabled identification of speed and strategy use on the addition facts, grouped into eight fact bundles (e.g. zeroes, small doubles), as a parsimonious procedure for exploring processing efficiency. Profiles of children based on latency performance on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 64 publications
(101 reference statements)
0
22
0
2
Order By: Relevance
“…For instance, knowing the multiplication table by heart can help in solving more advanced mathematics problems by reducing the cognitive load, or mental effort, in learners. In short, by helping students to retain and retrieve basic mathematics facts, rules and procedures, repetitive learning and memorisation can help students to solve mathematics problemseven the most complex -more efficiently (Cumming and Elkins, 1999). These benefits might explain why, in some education systems, particularly those in East Asia, many people believe that memorisation is compatible with creativity, understanding and a deep approach to mathematics learning, and why it has been described as the "springboard of learning" (Biggs, 1998;Hess and Azuma, 1991;Jin and Cortazzi, 1998;Kember, 1996;Orlin, 2014;Sadler-Smith and Tsang, 1998).…”
Section: Practice Makes Perfect…mentioning
confidence: 99%
“…For instance, knowing the multiplication table by heart can help in solving more advanced mathematics problems by reducing the cognitive load, or mental effort, in learners. In short, by helping students to retain and retrieve basic mathematics facts, rules and procedures, repetitive learning and memorisation can help students to solve mathematics problemseven the most complex -more efficiently (Cumming and Elkins, 1999). These benefits might explain why, in some education systems, particularly those in East Asia, many people believe that memorisation is compatible with creativity, understanding and a deep approach to mathematics learning, and why it has been described as the "springboard of learning" (Biggs, 1998;Hess and Azuma, 1991;Jin and Cortazzi, 1998;Kember, 1996;Orlin, 2014;Sadler-Smith and Tsang, 1998).…”
Section: Practice Makes Perfect…mentioning
confidence: 99%
“…Those standards are supposed to be "mastered" by the end of that school year. This research, along with others (Cumming & Elkins, 1999;Lin & Kubina, 2005;Stickney et al, 2012;Woodward, 2006), shows a different situation. Our math students are struggling when they are in elementary school, they are struggling when they are in middle school, and by the time they are in high school, they are years behind.…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, fact fluency is of high importance for problem-solving and conceptual understanding (Cumming & Elkins, 1999;Kilpatrick et al, 2001;NMAP, 2008;Woodward, 2006). Difficulties in achieving fluency in multiplication facts are often reported by students and teachers, however, and findings that may aid this process would be welcome in many classrooms (Kilpatrick et al, 2001;Wallace & Gurganus, 2005).…”
Section: Educational Implicationsmentioning
confidence: 98%
“…As well as affecting problem-solving, research has shown that inefficient solving of basic facts depletes resources that are needed for acquiring more advanced computational skills, such as those required for multi-digit sums (Cumming & Elkins, 1999). Weak ability to retrieve arithmetic facts can also impede children's ability to follow mathematical discourse and consequently to understand concepts that are introduced in class, such as equivalence, the commutative property and other concepts that form the basis of more advanced mathematics, such as algebra (Gersten, Jordan, & Flojo, 2005;NMAP, 2008;Woodward, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation